The effects of various grit limestone feeding on egg yield and egg shell quallty in different laying hybrids - Behiç Çoşkun; Kaan M. İşcan; Varol Kurtoğlu; Seval Apaydın (Eurasian Journal of Veterinary Sciences)
In this study, total 324 layıng hens were used. Hens were dıvıded 9 groups to 3x3 factorial design. Three commercial laying hybrits groups were Hysex Brown (HB), Hyline W-77 (HY) and Babcock B-300 (BB) and 3 varıous limestone feedıng groups were 8.5 % finely ground limestone (K), 8.5 % grit limestone (G) and 8 5 % fınely ground lımestone + ad lib. grıt limestone (+G). Laying performanca and egg shell quality were measured during 12 months Egg yield of +G was lower than the others (p<:0.01). But significant interaction was found between hybrid and feeding groups (p<0.05). The negative effect of +G was not seen in HY group. Spe· sifıc gravıty (SG) of +G was hıgher than other two groups (p<0.01 ). SG values were 1 086, 1 084, 1.087 g/cm3 respecııvely, ın groups HB. HY, BB Avarege egg weight of HB was the heavıest than the other two hybrıds +G group concumed more feed for 1 kg egg than K group. this values found as 2 00. 2.10 2 15 kg, respectıvely, in K, G and +G groups There were no signıfıcanı dıfferences in mortalıty rates among groups Asa result the posıtive effects of ad lib. grit lımestone feedıng was seen in HY hybrid but in the other hybrids. ground lımestone was given the best result.